2020
DOI: 10.1002/cctc.202001333
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Design of Hybrid Polymer Catalysts with Multicopper Sites for Oxygen Reduction

Abstract: Cu-containing metalloenzymes are known to catalyze oxygen activation through cooperative catalysis. In the current work, we report the design of synthetic polymer Cu catalysts using pyrene-labelled poly(2-hydroxy-3-dipicolylamino) propyl methacrylate (Py-PGMADPA) to coordinate multiple Cu sites along polymer chains. The catalysts feature a pyrene end group that can form supramolecular π-π stacking with conductive carbon to allow efficient immobilization of catalysts to the graphite electrode. Cu-containing Py-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 51 publications
(60 reference statements)
2
14
0
Order By: Relevance
“…In the electrochemical reduction of O 2 , H 2 O 2 can be synthesized by a two-electron transfer process: O 2 + 2H + + 2e – → H 2 O 2 , E ° = 0.695 V vs the reversible hydrogen electrode (RHE). While an oxygen reduction reaction (ORR) on metal catalysts often involves a four-electron transfer, controlling the spatial distribution of noble metals like isolated Pd sites has shown to be very selective in reducing O 2 by a two-electron transfer. , A similar perspective is demonstrated in earth-abundant metal-based catalysts, e.g., molecular Cu catalysts. , It has been reported that H 2 O 2 production can be stimulated by changing the surrounding atomic structure of the metal center . By fine-tuning the environment and the local interactions of the metal site, highly active early transition metal catalysts have been reported for H 2 O 2 production. , …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the electrochemical reduction of O 2 , H 2 O 2 can be synthesized by a two-electron transfer process: O 2 + 2H + + 2e – → H 2 O 2 , E ° = 0.695 V vs the reversible hydrogen electrode (RHE). While an oxygen reduction reaction (ORR) on metal catalysts often involves a four-electron transfer, controlling the spatial distribution of noble metals like isolated Pd sites has shown to be very selective in reducing O 2 by a two-electron transfer. , A similar perspective is demonstrated in earth-abundant metal-based catalysts, e.g., molecular Cu catalysts. , It has been reported that H 2 O 2 production can be stimulated by changing the surrounding atomic structure of the metal center . By fine-tuning the environment and the local interactions of the metal site, highly active early transition metal catalysts have been reported for H 2 O 2 production. , …”
Section: Introductionmentioning
confidence: 96%
“…On top of the typical time-consuming separation and recycling of anthraquinone, the long-term storage of relatively unstable H 2 O 2 is problematic. There are a number of catalytic and noncatalytic processes to produce H 2 O 2 in controlled quantitative yield. For example, electrochemical synthesis of H 2 O 2 from O 2 is effective, controllable, and, more importantly, can be done on demand . In the electrochemical reduction of O 2 , H 2 O 2 can be synthesized by a two-electron transfer process: O 2 + 2H + + 2e – → H 2 O 2 , E ° = 0.695 V vs the reversible hydrogen electrode (RHE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] In this paper we report a cascade reaction using electrocatalytically produced hydrogen peroxide that activates HRP to drive biocatalytic oxidation with high chiral selectivity. A synthetic catalyst, Cu 2 + -containing pyrene-labelled poly(2hydroxy-3-dipicolylamino) propyl methacrylate (PyÀ PGMA 49 DPA) that we recently synthesized, [19] electrochemically reduces oxygen in solution to hydrogen peroxide (Scheme 1). HRP crosslinked with polylysine in LbL films on 1 μm carboxylated magnetic beads (MPs) was activated by hydrogen peroxide to drive the epoxidation of styrene and the CÀ H bond oxidations of ethylbenzene and methyl phenylacetate.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of natural enzymes for many organic reactions, however, is very limited due to low stability, poor recyclability, and solubility under non-aqueous and high-temperature conditions. 11 As inspired by nature, extensive efforts have been contributed to create synthetic metallopolymer catalysts with a microenvironment for catalytic sites (often metal ions or nanoparticles), such as micelles, [12][13][14][15][16][17] single-chain polymer nanoparticles (SCNPs), [18][19][20][21][22][23][24][25][26][27][28][29] and dendrimers. [30][31][32][33] Among those, polymer micelles have unique nanostructures derived from amphiphilic block polymers (BCPs), of which the hydrophobic segment spontaneously aggregates to form core-shell assemblies in water.…”
Section: Introductionmentioning
confidence: 99%